Keragaman Genetik dan Hubungan Kekerabatan 12 Aksesi Kina (Cinchona ledgeriana) Asal Biji Berdasarkan Karakter Morfologi - Dinda Rachmatis Sa'adah; Yudithia Maxiselly; Muhamad Khais Prayoga; Heri Syahrian; Vitria Puspitasari Rahadi (Jurnal Penelitian Teh dan Kina, 2025)
Quinine (Cinchona ledgeriana) is a plantation plant with potential alkaloid content. The potential of quinine plants in the industrial sector is quite large, especially the beverage industry. This condition needs to be accompanied by an increase in quinine productivity, one of which is the maintenance of germplasm collections. Efforts to assemble superior clones from genetic material of seed origin require information on genetic diversity and the level of kinship. The purpose of this study was to determine the genetic diversity and kinship of accessions of seed-derived quinine germplasm based on morphological characters. This research was conducted in November 2023 - January 2024 at the Gambung Tea and Kina Research Center, Pasir Jambu District, Bandung Regency, West Java. A total of 12 accessions selected in the population were identified morphological appearance of 6 characters. The level of kinship of the 4 clone elders of the quinine germplasm collection was determined by Principal Component Analysis (PCA) and Cluster Analysis using XlStat software. The results obtained are 12 collections of quinine germplasm of seed origin that have been studied have diversity in morphological characters of plant height, stem diameter, number of leaves, leaf area, and stem bark thickness. The seed-origin quinine plant population has a wide genetic diversity based on its morphological characters. This is shown by the total PC value in PC 1 and PC 2 of 70.59%. Through cluster analysis, 12 accessions of quinine seed origin from 4 elders were divided into 2 large groups. Group 1 dominates the population group, which is 66.7% of the 12 accessions.